Music in the War: The Messages of the "Contras'" Songs - Fernández Ampié, Guillermo (Meridional. Revista Chilena de Estudios Latinoamericanos, 2024)
This article offers an initial analysis of the songs sung by members of the Nicaraguan Resistance, an anti-Sandinista group better known as “la Contra”. This irregular army was organized and funded by the United States to wage war and overthrow the Nicaraguan government, which was led the Sandinista Front after Anastasio Somoza Debayle’s dictatorship was overthrown in July 1979. The analysis of the songs argues that in the bloodiest years of the conflict, the issues of land claims and the defense of traditional ways of life - which have been considered by recent studies to be the main motivation for their struggle - were not present in cultural expressions like songs and hymns.The text is divided into five sections. The first offers a synthesis of the presence of music in war in general. The second focuses more specifically on Latin America, and addresses the way music and singing has been used in different popular movements and guerrilla organizations to express the objectives of their struggle. The third highlights the role of music in the Nicaraguan revolutionary struggle, while the fourth discusses the songs of the counterrevolutionary forces. In this way, we will show how the “contras” represented, in these musical expressions, their aspirations, experiences and the meaning of their struggle. The methodology used includes research into digital archives and interviews and consultations with former members of the anti-Sandinista forces. The article closes with a section of final reflections.